Construction of High-Quality Integration Mechanism Between Red Study Tour and "Mobile Ideological and Political Courses" in Heilongjiang Province Under the Strategy of Building a Powerful Country in Education——Based on the Investigation and Reflection of Patriotic Thematic Education Activities in Hunan, Jiangxi and Shaanxi Provinces - Bin Yu; Yongbo Yuan; Dan Wang (Education Research on Study Tours and Practice, 2026)
Under the guidance of the strategy of building a leading educational country, the in-depth integration of red study tours and "mobile ideological and political courses" has become a core proposition for expanding the space of practical education. Taking situated learning theory, the experiential learning cycle model and collaborative governance theory as the analytical framework, this paper conducts a systematic investigation of patriotic themed educational activities in Hunan, Jiangxi and Shaanxi Provinces. It examines their advanced experience featuring provincial overall planning, financial guarantee and departmental coordination, and meanwhile reveals the prevalent limitations of the "Version 1.0" stage, such as superficial learning methods and fragmented disciplinary knowledge.The study finds that Heilongjiang Province boasts profound endowments for constructing an integrated characteristic model, including the spirit of the Northeast Anti-Japanese Allied Forces, the Daqing Iron Man spirit, the Beidahuang spirit, as well as cold-region ice and snow resources. Nevertheless, it is currently confronted with bottlenecks such as superficial integration, fragmented curriculum arrangement, and weak and scattered support systems.Based on Tyler’s curriculum rationale and Xu Xuemei’s interdisciplinary project-based learning theory, this paper innovatively proposes a high-quality integration mechanism featuring "two-wheel driving" (policy-driven + curriculum innovation-driven) and "five-dimensional collaboration" (management, curriculum, teachers, evaluation and support). It promotes the strategic upgrading of practical education from "scenario explanation" to "interdisciplinary inquiry-based learning". By designing in-depth practical courses that enable learning by doing, learning by creating and learning by debating, improving the provincial smart management platform and refining reward and subsidy policies, the fundamental goal of fostering morality and shaping people in a heartfelt and effective manner can be ultimately achieved. This research provides a referable "Longjiang Model" for the regional implementation of the strategy of building a leading educational country.